Nocardia prophylaxis, treatment, and outcomes of infection in lung transplant recipients: A matched case‐control study - Goodlet, Kellie J.; Tokman, Sofya; Nasar, Aasya; Cherrier, Lauren; Walia, Rajat; Nailor, Michael D. (Transplant infectious disease, 2021)
Background Lung transplant recipients are at heightened risk for nocardiosis compared to other solid organ transplant recipients, with incidence rates as high as 9% and up to 30% associated mortality. No controlled studies assessing risk factors for nocardiosis in this high‐risk population have been reported. Methods Patients undergoing lung transplantation at a single center between 2012 and 2018 and diagnosed with nocardiosis post‐transplant were matched 1:2 to uninfected control subjects on the basis of age, transplant date, and sex. Results The incidence of nocardiosis in this lung transplant population was 3.4% (20/586), occurring a median of 9.4 months (range 4.4‐55.2) post‐transplant. In multivariable analysis, consistent use of trimethoprim/sulfamethoxazole (TMP/SMX) in the 12 weeks prior to diagnosis was independently associated with protection against nocardiosis (OR 0.038; 95% CI 0.01‐0.29; P = .002). Augmented immunosuppression in the 6 months prior to diagnosis was independently associated with the development of nocardiosis (OR 9.94; 95% CI 1.62‐ 61.00; P = .013). Six case patients (30%) had disseminated disease; all‐cause 6‐month mortality was 25%. The most common species was Nocardia farcinica (7/17 isolates), which was associated with dissemination and mortality. The most active antibiotics were TMP/SMX (100%), linezolid (100%), and amikacin (76%). Imipenem was only active against 4/17 isolates (24% susceptibility), with two isolates becoming non‐susceptible later in therapy. Conclusions Trimethoprim/sulfamethoxazole prophylaxis was shown to be protective against nocardiosis in lung transplant recipients, while augmented immunosuppression conferred increased risk. Institutional epidemiologic data are needed to best guide empiric therapy for Nocardia, as historical in vitro data may not predict local susceptibilities.